On the Existence of a Finite Base for Complete Trace Equivalence over BPA with Interrupt - Aceto, Luca; Capobianco, Silvio; Ingólfsdóttir, Anna (BRICS Report Series, 2007)
We study Basic Process Algebra with interrupt modulo complete trace equivalence. We show that, unlike in the setting of the more demanding bisimilarity, a ground complete finite axiomatization exists. We explicitly give such an axiomatization, and extend it to a finite complete one in the special case when a single action is present.